2006
DOI: 10.1086/506398
|View full text |Cite
|
Sign up to set email alerts
|

The Postoperative Bacteriuria Score A New Way to Predict Nosocomial Infection After Prostate Surgery

Abstract: POBS could be used to distinguish patients at risk of developing infection after TURP. This information might be useful for implementing selective prevention measures or for adjustment for differences in nosocomial infection rates when comparing data between urology centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
1
22
1
6
Order By: Relevance
“…After an aerobic incubation at 37˚C, the plates showing significant growth as per the Kass count (single species count of more than 10 5 organisms per ml of urine) were processed further and the isolates were identified up to the species level by using standard biochemical tests [5][6][7][8]. Antibiotic sensitivity testing was done by the Kirby Bauer disc diffusion method as per CLSI guidelines [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…After an aerobic incubation at 37˚C, the plates showing significant growth as per the Kass count (single species count of more than 10 5 organisms per ml of urine) were processed further and the isolates were identified up to the species level by using standard biochemical tests [5][6][7][8]. Antibiotic sensitivity testing was done by the Kirby Bauer disc diffusion method as per CLSI guidelines [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial count was expressed as colony forming units (CFU) per milliliter (ml). Following the recommendations of Kass in distinguish in the infection from contamination, significant bacteriuria was defined as culture of a single bacterial species from the urine sample at a concentration of >10 5 CFU/ml [11].…”
Section: Direct Microscopymentioning
confidence: 99%
“…This is not supported by our study, where duration of the surgery was not a risk factor (p=0.332). This is supported by Girou et al 31 Urological departments should be encouraged to monitor the susceptibility of pathogens causing NAUTI in order to overcome the possibility of infection. Overall, the risk factors fall into three general categories: patient-related risk factors, device-related risk factors, and risk factors related to catheter insertion and care.…”
Section: Closed Drainagementioning
confidence: 87%
“…2 Several authors have, however, reported that TURP represents a risk factor for NAUTI. 30,31 The duration of surgery has long been implicated in nosocomial infections. This is not supported by our study, where duration of the surgery was not a risk factor (p=0.332).…”
Section: Closed Drainagementioning
confidence: 99%